Ethnobotany Database: Exploring Diversity Medicinal Plants of Dayak Tribe Borneo - Haeruddin Haeruddin; Ummul Hairah; Edy Budiman; Herni Johan (IAES Indonesia Section, 2017)
This study aimed to collect data and information of the Ethnobotany Dayak Tribe, in particular, development of the database which can be used as a media explorer for exchange information society on Borneo's biodiversity and in an attempt preserving of culture local wisdom in traditional medicine so that not extinction. Ethnobotany database collected from various scientific literature, results of report ethnobotany from Related institutions, field study, journals available in the text form, and local wisdom culture of the Dayak tribe. database system development methodology using to the software engineering framework model, with representation standard data model for taxonomic information refer to International Code of Nomenclature for algae, fungi, and plants (Melbourne Code). To date, data has been collected as many as 233 species records from45 ethnic Dayak, with datasets; plant species, family name, identification, taxonomy ID from NCBI, geographical occurrence,plant parts used, ethnobotany importance, morphological characteristics, local name, the efficacy of medicinal plants, chemical values, distribution, locations, data sources, references, and descriptions related to the medicinal plants.